Scientific attitudes in chemistry learning: A systematic literature review - Intan Shanderi; Suwardi Suwardi (Pascasarjana Universitas Negeri Medan, 2023)
This systematic review analysis study aimed to examine the scientific attitudes in chemistry learning. The method used a Systematic Literature Review which consists of 5 stages adopted from Denyer and Tranfield. The main criteria for the selection of articles are scientific attitude in the field of chemistry learning with a period of 2012 until 2023 from the well-known national and international database. There were 29 articles were obtained that fit into the criteria. The article’s aspect focused on the parameters such as aim, sample level, instructional method, instruments, and chemistry subject. The result showed that the attitude scale is the most instrument that can be used to measure scientific attitude in chemistry learning. Meanwhile, PBL has become the most instructional method that has been used to enhance scientific attitude. Moreover, the studies mostly aim to investigate the influence of teaching methods on scientific attitudes. Most researchers involve high school students in scientific attitude research on analytical chemistry concepts. There are different codes for each theme of scientific attitudes. Thus, the review helps to evaluate the instrument and instructional methods in chemistry learning and also provides recommendations for examining students’ scientific attitudes in further explorations.Keywords: Chemistry learning; Instructional method; Instrument; Scientific attitudes